Antiviral drug screen identifies DNA-damage response inhibitor as potent blocker of SARS-CoV-2 replication - Garcia, Gustavo, Jr.; Sharma, Arun; Ramaiah, Arunachalam; Sen, Chandani; Purkayastha, Arunima; Kohn, Donald B.; Parcells, Mark S.; Beck, Sebastian; Kim, Heeyoung; Bakowski, Malina A.; Kirkpatrick, Melanie G.; Riva, Laura; et al. (Cell reports, 2021)
SARS-CoV-2 has currently precipitated the COVID-19 global health crisis. We developed a medium-throughput drug-screening system and identified a small-molecule library of 34 of 430 protein kinase inhibitors that were capable of inhibiting the SARS-CoV-2 cytopathic effect in human epithelial cells. These drug inhibitors are in various stages of clinical trials. We detected key proteins involved in cellular signaling pathways mTOR-PI3K-AKT, ABL-BCR/MAPK, and DNA-damage response that are critical for SARS-CoV-2 infection. A drug-protein interaction-based secondary screen confirmed compounds, such as the ATR kinase inhibitor berzosertib and torin2 with anti-SARS-CoV-2 activity. Berzosertib exhibited potent antiviral activity against SARS-CoV-2 in multiple cell types and blocked replication at the post-entry step. Berzosertib inhibited replication of SARS-CoV-1 and the Middle East respiratory syndrome coronavirus (MERS-CoV) as well. Our study highlights key promising kinase inhibitors to constrain coronavirus replication as a host-directed therapy in the treatment of COVID-19 and beyond as well as provides an important mechanism of host-pathogen interactions.
Gesehen am 18.05.2021